Environmental Toxicology and Risk Assessment: Modeling and Risk Assessment Sixth Volume 1997
DOI: 10.1520/stp12230s
|View full text |Cite
|
Sign up to set email alerts
|

A Food Web Model of Mercury Transfer from Stream Sediment to Predators of Fish for Ecological Risk Based Clean-Up Goals

Abstract: A linear steady state model of the food web linking sediment to piscivorous predators was used to derive ecological risk based clean-up concentrations for mercury in sediment of East Fork Poplar Creek (EFPC), Oak Ridge, TN. The model partitions aquatic invertebrates into two classes based on the primary source of exposure to mercury in sediment, and the prey-fish community into three classes based on differences in their diets and feeding habits. Biotransfer factors for the links between sediment and sediment-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
0
6
2
Order By: Relevance
“…They found that more than 80% of methylmercury exposures were less than the lowest‐observed‐adverse‐effect‐level (LOAEL)‐based dietary limits for great blue herons and kingfishers and less than the no‐observed‐adverse‐effect‐level (NOAEL)‐based dietary limits for mink. Some of the difference in our results and those of Burns et al [7] can be attributed to differences in approach (e.g., food web model vs tissue residues to estimate exposures and hypothesis testing vs regression methods to estimate toxic effects doses). However, a more likely explanation is that sediment is a relatively minor exposure pathway compared to water [4].…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…They found that more than 80% of methylmercury exposures were less than the lowest‐observed‐adverse‐effect‐level (LOAEL)‐based dietary limits for great blue herons and kingfishers and less than the no‐observed‐adverse‐effect‐level (NOAEL)‐based dietary limits for mink. Some of the difference in our results and those of Burns et al [7] can be attributed to differences in approach (e.g., food web model vs tissue residues to estimate exposures and hypothesis testing vs regression methods to estimate toxic effects doses). However, a more likely explanation is that sediment is a relatively minor exposure pathway compared to water [4].…”
Section: Discussioncontrasting
confidence: 93%
“…Using a sediment‐based food web model for EFPC, Burns et al [7] did not find that methylmercury posed a significant risk to piscivorous species. As with our analysis, Burns et al [7] used Monte Carlo analysis to quantify the uncertainty in the predicted exposure of an average individual for several top predator species. However, their results differed greatly from those shown in Figures 2D and 4D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under CERCLA, remedial options must be developed and evaluated with regard to their costs of implementation and effectiveness at reducing risks to biota [4]. Previous assessments at EFPC demonstrated that mink (Mustela vison) and belted kingfishers (Ceryle alcyon) may face significant risks from exposure to mercury and PCBs, mainly because both organisms are at the top of the aquatic food chain and mercury and PCBs are persistent and bioaccumulative [4][5][6][7]. Mink are also known to be especially sensitive to organochlorines [8,9] and methylmercury [10].…”
Section: Introductionmentioning
confidence: 99%